Effect of hypoeutectic boron modification on the dynamic properties of Ti-6Al-4V alloy. Issue 18 (4th July 2016) - Bommakanti, Aashranth; Roy, Shibayan; Suwas, Satyam
Abstract: Abstract : The effect of boron on the room-temperature dynamic properties of Ti-6Al-4V alloy with and without boron addition in as-cast and β-forged conditions is studied by varying number of loading cycles, frequency of loading, and strain amplitude. Boron addition seems to lower the complex modulus and increases the damping of the base Ti-6Al-4V alloy. TiB precipitates in boron modified alloys play a key role in improving the damping through dislocation pinning (at all frequencies) and grain boundary pinning (at high frequencies). These effects are more prominent after β-forging wherein arrangement of TiB particles is found to be a deciding factor. Strain amplitude variation of damping shows trend reversal between 10 and 87 Hz frequencies; damping increases with strain amplitude at 10 Hz but reduces with strain amplitude at 87 Hz. A damping peak occurs near the 50 Hz frequency, and cycling through this range results in a significant improvement in damping (21% for as-cast and 93% for β-forged alloys).